Galactorrhea: how to address this unusual complication after augmentation mammoplasty - Adriana Sayuri Kurogi Ascenço; Ruth Graf; Ivan Maluf Junior; Priscila Balbinot; Renato da Silva Freitas (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Galactorrhea and galactocele formation after breast augmentation are complications reported in the literature, but the cause remains unknown. METHODS: We present a case of a 28-year-old patient who underwent breast augmentation surgery via the inframammary fold with an implant placed in the subfascial plane, which developed galactorrhea from the incision on the seventh postoperative day, and we propose an algorithm for the diagnosis and treatment of galactorrhea after mammoplasties. RESULTS: The complication was treated with the use of a lactation suppressor, cabergoline, presenting good outcomes. CONCLUSION: Galactorrhea is an uncommon complication after augmentation mammoplasties, which should always be considered in cases of secretions from an incision because it is a differential diagnosis for infections.